PENERAPAN METODE BILQOLAM UNTUK PENINGKATAN BACAAN AL-QUR’AN SISWA-SISWI SD ISLAM TERPADU IQRO KARANGPLOSO-MALANG - Ushuludin Baharsyah Baharsyah; Akhmad Said (STAI Ma'had Aly Al-Hikam Malang, 2022)
Al-Qur'an development education cannot be separated from the Qur'anic learning method. In this study, the researcher chose the Bilqolam method to study because many of the formal educational institutions cooperated with Bilqolam, especially in the Malang area. Meanwhile, as a place of research, researchers are motivated to conduct research on the application of Bilqolam at SD Islam Terpadu Iqro Karangploso-Malang because Bilqolam is used as intracurricular. This research was conducted to find out how the implementation of Bilqolam. The research approach used by the researcher is a qualitative approach with a case study type. Data collection is done by interview, observation, and documentation. Check the validity of the data are triangulation, and confermability. The result of the research is that the school made a slight modification of the duration of Bilqolam teaching time.